Non-linear dependence in the Malaysian stock market - Lim, Kian Ping; Habibullah, Muzafar Shah; Lee, Hock Ann (Universiti Putra Malaysia Press, 2005)
This study empirically investigates the presence of non-linearity in the Malaysian stock market, employing the Brock-Dechert-Scheinkman (BDS) and Hinich bispectrum tests. The BDS results reveal that the characteristics of the returns series in the Malaysian stock market are driven by non-linear mechanisms. Subsequent application of the Hinich bispectrum test confirms the results of the BDS test. The result of the present study has strong implications on the empirical work involving the Malaysian stock market as the existence of non-linearity suggests the inappropriateness of using linear methods for drawing inferences.